Toxic effect of xylene exposure on reticulin fibres in sprague dawley rat liver - Yasrul Izad, Abu Bakar; Mohd Harissal, Ismail; Nurul Aiman, Mohd Yusof; Hasmah, Abdullah (2019)
Introduction: This study was to investigate the tom effect of xylene exposure on the ever ossue of Sprague-Dawiey rats. Materials and Methods: Twelve 28 day-old Sprague-Cawley rats were divided into control and gene group. The xylene group was given 8.47mmolfkg/day of )(One in olive col vehicle while the control group received only olive oil vehicle Via oral route for 2 weeks. Then, the rats were sacrificed, arid the sections of liver were stoned with reticulin staining. The fine structure of sectioned specimens from the fiver was investigated under microscope for qualitative analysis Results and Discussion: The study revealed that xylene exposure had caused a reduction in reticufin fibres of the Irver. Reacultn crowding areas therefore showed focal loss of hepalocyles Large areas of cell necrosis appeared as rebculin collapsed. Conclusion: The reecuen start provides important information about the archnecon of two Irver as rowan prowies the stromal support for the parenchyma. When hepalocytes are damaged and undergo necrosis. they collapse n the empty space left behind by the refs:Win fibres surrounding them